2015
DOI: 10.1007/s11999-015-4248-3
|View full text |Cite
|
Sign up to set email alerts
|

Do Sex Differences Exist in Rates of Falls and Fractures in Hutterite, Rural, and Nonrural Populations, Aged 20 to 66 Years?

Abstract: Background Falls and fractures are a major public health concern with an economic impact of more than USD 19 billion per year. Extensive research into the risk of falls and fractures in elderly populations has been performed; however, little is known about fall or fracture risk in younger populations. Additionally, sex-and population-specific (rural versus nonrural) fall and fracture risk may be important in identifying groups most at risk in an effort to develop preventive measures. Questions/purposes The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…The relative increase of lower extremity fractures' frequency after the age of seventy may be explained by the exponential increase in hip fractures, which was previously reported to occur due to a variety of factors: Decreased bone quality, impaired neuromuscular responses, and increased risk of falling. [3,16,19] On the one hand, the rates of open and pathological fractures were also reported in the present study, as 11.6% and 1.8%, respectively. On the other hand, the overall mortality rate related with adult fractures was also found as 0.4%.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The relative increase of lower extremity fractures' frequency after the age of seventy may be explained by the exponential increase in hip fractures, which was previously reported to occur due to a variety of factors: Decreased bone quality, impaired neuromuscular responses, and increased risk of falling. [3,16,19] On the one hand, the rates of open and pathological fractures were also reported in the present study, as 11.6% and 1.8%, respectively. On the other hand, the overall mortality rate related with adult fractures was also found as 0.4%.…”
Section: Discussionsupporting
confidence: 85%
“…[ 3 , 13 15 ] Conversely, it was demonstrated that males aged 39 and younger had 135% greater fall risk than females in the same age category and that no sex differences were observed for fracture risk. [ 16 ] However, the results of this study may be challenged by their report being in a much smaller population in a limited geographical region, compared with other studies. The only female predominance was in proximal humerus (AO/OTA 11) fractures in our study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Comparison of the role of sex and age in OP/OF and in HPI is of interest. OP/OF affects more females in the older/postmenopausal age (the F:M ratio among hip fracture patients is 2:1 [ 401 ]) and the incidence of OFs increases exponentially with age >70 years in both genders [ 402 , 403 , 404 , 405 ], while males <40 years of age had higher fall rates [ 406 ]. Among adults, a small male predominance of HPI-related outcomes has been found in a meta-analysis based on 169 studies (OR 1.12, 95% CI: 1.09, 1.15) [ 407 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%